Brief approaches to genetic integrity - Bendezú Gómez, Reenzo (2018)
Genetic integrity is a natural virtue that every human being has, which allows him to keep his body healthy, without any affectation or diminution of his body parts. In turn, it also protects the integrity and preservation of the species and the human genome.